Ukhuwah: Manajemen Nabi Meretas Perbedaan - Ali Nurdin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2005)
The justification of religion in a conflict, especially conflicts arising among followers of different religions, often surfaces easily. They frequently invoke religion by raising sacred symbols, masses, or groups to attempt to eliminate other groups. These conflicts often end in bloodshed. In such conditions, an interesting concept in Islamic teachings can be applied to overcome it, namely Ukhuwah Islamiyah (Islamic brotherhood). This brotherhood has been exemplified by the Prophet and his companions. They truly understood its meaning and embodied it in their lives, thus creating peace, harmony, and coexistence among them, both within the religion and among people of different faiths.